In vivo evaluation and dosimetry of 123I-2-iodo-D-phenylalanine, a new potential tumor-specific tracer for SPECT, in an R1M rhabdomyosarcoma athymic mouse model. - Kersemans, V; Cornelissen, B; Bacher, K; Kersemans, K; Thierens, H; Dierckx, R; De Spiegeleer, B; Slegers, G; Mertens, J (2005)
UNLABELLED: Earlier reports described the preferential uptake of d-amino acids in tumor-bearing mice. Moreover, it was shown that in tumor cells in vitro the L-amino acid transporter system seemed to lack stereospecificity. Because of the successful results with 123/125I-2-iodo-L-phenylalanine, 123/125I-2-iodo-D-phenylalanine was developed, and its tumor-detecting characteristics were evaluated in vivo. METHODS: 123I labeling of 2-iodo-D-phenylalanine was performed with a kit formulation by use of Cu1+-assisted nucleophilic exchange. 123I-2-Iodo-D-phenylalanine was evaluated in R1M tumor-bearing athymic mice by dynamic planar imaging (DPI) and dissection. The in vivo stability of the tracer was tested by high-performance liquid chromatography. Tumor tracer retention and tracer contrast were evaluated as a function of time. Two-compartment blood modeling from DPI results and dosimetric calculations from biodistribution results were carried out. Moreover, 125I-2-iodo-D-phenylalanine and 18F-FDG uptake in acute inflammation was investigated. RESULTS: 123I-2-Iodo-D-phenylalanine was metabolically stable. Fast, high, and specific tumor retention was observed. Two-compartment modeling confirmed the fast clearance of the tracer through the kidneys to the bladder, as observed by DPI and dissection. Moreover, compared with the L-isomer, 123I-2-iodo-D-phenylalanine demonstrated faster clearance and faster uptake in the peripheral compartment. No accumulation in the abdomen or in the brain was noted. Dosimetry revealed that 123I-2-iodo-D-phenylalanine demonstrated a low radiation burden comparable to those of 123I-2-iodo-L-phenylalanine and 123I-2-iodo-L-tyrosine. Although 123I-2-iodo-D-phenylalanine showed a tumor retention of only 4%, the tumor contrast was increased up to 350% at 19 h after injection. CONCLUSION: 123I-2-Iodo-D-phenylalanine is a promising tracer for diagnostic oncologic imaging because of its high, fast, and specific tumor uptake and fast clearance from blood.